Expansion of Harmonic Wave ln the Wedge with Random Vertical Angle - Djumaev Zokir Fatilloyevich; Fatiloev Sardor Zokirovich (International Journal on Human-Computing Studies, 2021)
The article covers the expansion of harmonic waves in the deformable wedge. A spectral problem is formulated, which is solved numerically. The article reports the development of the method for solving the problem, the action of elastic wave on cylinder with a radial crack by limiting case of wedge with angle of 360° on bodies (shell) located in infinite linear-elastic medium, as well as its algorithms. Closed system of differential equations, as well as the corresponding initial and boundary conditions have been drawn. Obtained analytical results have theoretical and applied significance.